Nilai Tukar Nelayan Kabupaten Situbondo - Anita Diah Pahlewi; Ramli Ramli; Vita Novianti (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
Fishermen are very dependent on the season. Measuring the welfare of fishermen requires indicators that are quick and precise to see a picture of the welfare that has been achieved. One indicator that is believed to be used to see household welfare is the Fishermen's Exchange Rate (NTN) indicator. The purpose of this Fishermen's Exchange Rate research is to find out the characteristics of fishermen and the achievement of Fishermen's Exchange Rates in Situbondo Regency so that it can be used to provide input in the formulation of targets and formulation of policies to improve fishermen's welfare. The method used in this Fishermen Exchange Rate research is a survey. The number of respondents in the Fishermen Exchange Rate (NTN) Study was 189 respondents. The characteristics of the respondents in this study include the age group and educational level. Characteristics of fisherman respondents by age group consisted of 43% of fisherman respondents in the age group of 41-50 years, 22% in the age group of 30-40 years, 20% in the age group under 30 years and at least 15% in the age group of 51-60 years. The results of the analysis of the characteristics of fisherman respondents based on their level of education showed that the majority of respondents graduated from elementary school (SD) and below, namely 69%, 23% graduated from junior high school (SLTP) and only 8% had attended senior high school (SLTA) education. The NTN value of Situbondo Regency for the period January - October 2022 is 1.043 or the NTN value is around number one, which means that fishing families in Situbondo Regency in 2022 are only able to fulfill their daily needs and are categorized as vulnerable to poverty and are not yet able to consume secondary or tertiary needs, to save in the form of investment goods.